Kann das CT die Katheterangiografie für die Koronardiagnostik ersetzen? – Ja! - Ullrich, Helen; Gori, Tommaso (DMW - Deutsche Medizinische Wochenschrift, 2017)
The guidelines on the management of stable coronary artery disease (SCAD) recommend the use of coronary computed tomography angiography (CTA) in the process of diagnosing coronary artery disease in patients with low intermediate pre-test probability for SCAD. Particularly in cases where stress electrocardiogram or stress imaging provides unclear results, a computed tomographic examination can be considered as a reliable alternative to invasive coronary angiography. Due to its high negative predictive value, coronary CTA can provide accurate information on the presence of coronary artery stenosis and thus coronary artery disease can be reliably excluded without the risks associated with invasive procedures. Similarly, patients with unstable angina or chest pain without typical alterations in the electrocardiogram and without an elevation of troponin can also benefit from a non-invasive coronary CTA-based diagnostics as first approach as it allows ruling out the presence of disease or planning an intervention without the risks associated with a potentially inappropriate invasive approach.
Keywords: Computertomografie; Koronar-CT; Koronarangiografie; Koronare Herzkrankheit